2019
DOI: 10.1016/j.archger.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor disorders and health-related quality of life in older women: Results from the Women’s Gynaecological Health study in Lieto, Finland

Abstract: Objective: The aim of this study was to analyse the prevalence of pelvic floor disorders and to describe health-related quality of life(HRQoL)among older women. We also compared participants' HRQoL with the age-matched general female population and analysed factors associated with HRQoL.Study design: This is a population-based study of a cohort of women born in 1948 and in 1950 (n = 143) which is also part of the Women's Gynaecological Health study in Lieto, Finland. Methods: The data were collected by questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…POP may cause gas, liquid or fecal incontinence. 7,22 When we interpreted the results, we found that Wexner's fecal incontinence score changes were like ODS Altomare score. In the short time follow up, 3 months after surgery, the patients experienced very good results, but in the mean 1 year follow up, recurrence were very high.…”
Section: Discussionmentioning
confidence: 97%
“…POP may cause gas, liquid or fecal incontinence. 7,22 When we interpreted the results, we found that Wexner's fecal incontinence score changes were like ODS Altomare score. In the short time follow up, 3 months after surgery, the patients experienced very good results, but in the mean 1 year follow up, recurrence were very high.…”
Section: Discussionmentioning
confidence: 97%
“…Research has shown that the higher a patient's sense of shame, the more prominent their psychological issues and the lower their quality of life. 18 Therefore, healthcare professionals should have a deep understanding of the social alienation experiences of patients with SUI experiences with SIS. Approaching it from a positive psychology perspective, comprehensive team psychological therapies, 19 mindfulness-based stress reduction therapies 20 and other psychological measures can be employed to stimulate positive emotions, explore patients' inner potential, alleviate mental and physical stress, and reduce their level of social alienation.…”
Section: Current Status Of Social Alienation and Disease Stigma In Pa...mentioning
confidence: 99%
“…These symptoms are even more concerning in neurological patients, with a prevalence of 80% of patients having pelvic floor disorders [ 3 ]. These conditions have a negative impact on quality of life and in different areas of the patient’s life, such as the social, psychological, work, or sexual spheres [ 4 , 5 , 6 ]. In addition, these dysfunctions are common among the female world population [ 7 , 8 ], and their prevalence is expected to increase due to an increase in life expectancy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%